KOMPARASI HASIL BELAJAR MAHASISWA PROGRAM STUDI PENDIDIKAN SENI RUPA FAKULTAS BAHASA DAN SENI UNIVERSITAS NEGERI PADANG BERDASARKAN LATAR BELAKANG SEKOLAH ASAL - SISKA NOVIANTI, Dr. Ramalis Hakin, M.Pd., Dra. Ernis, M.Pd. (Serupa The Journal of Art Education, 2017)
This research the purpose to describe 1) The learning resulf of the college student who graduated from SMK. 2) The learning resulf of the college student who graduated from SMA/MA. 3) Differentes results of learning between college students who graduated from SMK, SMA/MA at Mayor of Fine Art in UNP accoding to the data analysis can be student that learning result of fine art mayor student who basically graduate from SMK are higher than the student who had SMA/MA.